Cost-efficient assessment of biomechanical exposure in occupational groups, exemplified by posture observation and inclinometry - Catherine Trask; Svend Erik Mathiassen; Jens Wahlström; Mikael Forsman (Nordic Association of Occupational Safety and Health (NOROSH), 2014)
OBJECTIVES: This study compared the cost efficiency of observation and inclinometer assessment of trunk and upper-arm inclination in a population of flight baggage handlers, as an illustration of a general procedure for addressing the trade-off between resource consumption and statistical performance in occupational epidemiology. METHODS: Trunk and upper-arm inclination with respect to the line of gravity were assessed for three days on each of 27 airport baggage handlers using simultaneous inclinometer and video recordings. Labor and equipment costs associated with data collection and processing were tracked throughout. Statistical performance was computed from the variance components within and between workers and bias (with inclinometer assumed to produce "correct" inclination angles). The behavior of the trade-off between cost and efficiency with changed sample size, as well as with changed logistics for data collection and processing, was investigated using simulations. RESULTS: At similar total costs, time spent at trunk and arm inclination angles >60 ° as well as 90^th percentile arm inclination were estimated at higher precision using inclinometers, while median inclination and 90th percentile trunk inclination was determined more precisely using observation. This hierarchy remained when the study was reproduced in another population, while inclinometry was more cost-efficient than observation for all three posture variables in a scenario where data were already collected and only needed to be processed. CONCLUSIONS: When statistical performance was measured only in terms of precision, inclinometers were more cost-efficient than observation for two out of three posture metrics investigated. Since observations were biased, inclinometers consistently outperformed observation when both bias and precision were included in statistical performance. This general model for assessing cost efficiency may be used for designing exposure assessment strategies with considerations not only of statistical but also cost criteria. The empirical data provide a specific basis for planning assessments of working postures in occupational groups.